Pengaruh Corporate Social Responsibility, Environmental Disclosure Dan Profitabilitas Terhadap Nilai Perusahaan Pada Emiten Energi Yang Terdaftar Di Bei Tahun 2020-2024 - Risca Olivianti; Pradita Andina Kurnia Putri; Maria Yovita R. Pandin (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) Disclosure Index, Environmental Disclosure Index, and profitability (Return on Assets/ROA) on company value in energy issuers listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The research uses a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method on 20 energy companies with a total of 100 data observations obtained through annual reports and capital market data. The results of the study indicate that the CSR Disclosure Index and Environmental Disclosure Index positively and significantly influence company value, indicating that social and environmental responsibility disclosures can enhance investor trust and corporate image. Additionally, profitability (ROA) also positively and significantly influences company value, confirming that financial performance remains a key factor in market valuation. Simultaneously, these three variables have a significant effect on company value, so it can be concluded that the integration of financial performance and sustainability disclosure is an important strategy for energy issuers in increasing company value and maintaining long-term business sustainability.